Las transferencias monetarias condicionadas y la desnutrición crónica infantil en América Latina - Cruz Polo, Esteban Nicolás (2025)
This research analyzes the effect of conditional cash transfers on chronic child malnutrition in 14 Latin American countries during the period 2009–2021. Chronic child malnutrition is a global public health issue that particularly affects children living in vulnerable contexts, leading to severe physical and cognitive consequences, and even death. In response, various governments have implemented conditional cash transfer programs aimed at mitigating the effects of this public health problem in society. To demonstrate the inverse relationship between the two variables, a panel data set was constructed, and fixed effects and random effects econometric models were estimated. The Hausman test determined that the most appropriate model is the random effects model. The results show that greater investment in these programs is associated with a significant reduction in the rate of chronic child malnutrition, supporting the assertions of economic theory.